SIMPLIFIED CONTROLLER DESIGN FOR OUTPUT PERFORMANCE UNDER COMMON INPUT LIMITATIONS WITH GENERALIZED INTEGRAL ANTI-WINDUP FOR A CLASS OF PROCESSES - Taworn Benjanarasuth (My University, 2020)
One of basic key tasks of a control system design is to achieve the desired output responses both in transient and steady states. Besides, the common input limitations, such as saturation and slew rate or at least avoiding a sudden jump in the command signal, must be considered in practice. However, popular controllers such as PI and PID cause sudden changes or even impulsive surges in the command signal under external excitations by a step reference input and/or step input/output disturbances. In this paper, a simplified controller design with its preferred structure models to meet the mentioned requirements is presented for a class of minimum-phase stable linear time-invariant single-input single-output processes with proper real rational transfer function. The structure of such controller is mathematically investigated and the result is that the controller must be strictly proper and containing an integral factor. The design procedure is simple and straightforward based on reference model matching and model cancellation with only two required conditions on the desired closed-loop transfer function which are its relative degree comparing to the processes to be controlled and the equality of the lower order coefficient(s) in its numerator and denominator polynomials. A generalized integral anti-windup structure, based on back calculation method and PI/PID anti-windup scheme, to lessen the saturation effect on the integral action of the proposed controller is additionally introduced by rearranging the controller in a parallel form with one separated integral control action portion. Numerical examples are investigated to demonstrate the design procedure and verify the success of the proposed controller to the required objectives.
Keywords: Internal model; Robustness; Minimum phase; Advanced Control Systems Design